United response of Lithuanian nation to J Stalin. - Pocius, Mindaugas (Genocidas ir rezistencija, 1998)
On 21 July 1940, the puppet ‘people’s’ Seimas, elected during fraudulent election, declared that the Soviet system was being established in Lithuania and decided to ask the Supreme Soviet of the USSR to admit the LSSR to the USSR as a union republic. The ‘voluntary accession’ took place. The propagandists of the LKP(b) proclaimed that the ‘people’s’ Seimas had thus expressed the will of the entire Lithuanian nation. In the summer of 1945, the Central Committee of the LKP(b) (apparently on the ‘advice’ of the LKP(b) office in Lithuania) had a good opportunity to show its slavish submission to the dictator Stalin on the eve of the 5th anniversary of the proclamation of Soviet power and the “incorporation of the LSSR into the union of the fraternal Soviet republics”. On this occasion, the leadership of the Central Committee of the Communist Party of Lithuania (LKP (b)) decided to send a letter of gratitude to Stalin, signed by the Lithuanian population. Although some agitators even threatened Siberia and the NKVD, the Lithuanians boycotted the signing of the letter in towns and countryside.
Keywords: Soviet occupation; antisoviet resistance; communist party; propaganda; terror